Molecular and Fitness Data Reveal Local Adaptation of Southern and Northern Estuarine Oysters (Crassostrea ariakensis) - Li, Ao; Wang, Chaogang; Wang, Wei; Zhang, Ziyan; Liu, Mingkun; She, Zhicai; Jia, Zhen; Zhang, Guofan; Li, Li (Frontiers in Marine Science, 2020)
Natural selection and genetic drift are both important for understanding the geographic distribution and environmental responses of marine species. In this study, we revealed distinct genetic variation in Crassostrea ariakensis by comparing the COI gene segment sequence in northern and southern oysters separated by the Yangtze River estuary. Reciprocal hybridization and intrapopulation crosses clarified their taxonomic status as the same species. There was no heterosis in the survival and growth of the hybrids, while the maternal effect was observed in larvae from eggs in the native habitat that showed higher fitness. Both the northern and southern F1 progenies exhibited positive performance in fitness traits, including survivorship, respiration rate, and growth, in their native habitats compared to that in their non-native habitats, indicating a strong signature of local adaptation. The oysters dwelling in the warm/southern habitats evolved a higher thermotolerance of LT50, while the oysters inhabiting the high-salinity/northern habitats had a 2.43‰ higher LS50 than that of their southern counterparts. After strong natural selection in the northern environments, the higher survival of the F1 progenies from the southern oysters under heat shock indicates an evolved genetic basis for its higher thermal tolerance. Strong environmental gradients, especially for temperature and salinity, and genetic drift of the interaction between coastal currents and the Yangtze River estuary potentially contribute to shaping the distribution pattern and adaptive divergence of C. ariakensis in China.